Quarternair CuGaSeTe and CuGa0.5In 0.5Te2 Thin Films Fabrication Using Flash Evaporation - Soepardjo, A. Harsono (Makara Journal of Technology, 2004)
Quarternair CuGaSeTe and CuGa0.5In 0.5Te2 Thin Films Fabrication Using Flash Evaporation. Quarternair materials CuGaSeTe and CuGa0.5In 0.5Te2 are the basic materials to solar cell fabrication. These materials have high absorption coefficients around 103 – 105 cm-1 and band gap energy in the range of 1-5 eV. In this research, the films were made by flash evaporation method using quarternair powder materials of CuGaSeTe and CuGa0.5In 0.5Te2 to adhere in a glass substrate. After the films were obtained, the properties of these films will be characterized optically and electrically. The lattice parameter of the films and the crystalline film structure were obtained using X-Ray Diffraction (XRD) spectroscopy. The XRD results show that the quarternair CuGaSeTe and CuGa0.5In 0.5Te2 films have a chalcopyrite structure. The absorption coefficient and the band gap energy of the films were calculated using transmittance and reflectance patterns that measured using UV-VIS Difractometer. The films composition can be detected by using the Energy Dispersive Spectroscopy (EDS), while the films resistivity, mobility and the majority carrier of the films were obtained from Hall Effect experiments.